CLINICAL AND LABORATORY DIAGNOSTICS OF CHRONIC BRONCHITIS IN CHILDREN - Ibragimova Nadiya Sabirovna; Isakulova Muhabbat Mardanovna; Xodjayeva Nargiza (Web of Journals Publishing, 2025)
The relevance of chronic bronchitis in children increases every year, which is associated with many factors affecting the health of the small population. Children, especially young children, are most susceptible to this disease due to the anatomy of the respiratory tract and the immaturity of the immune system. Chronic bronchitis, being a long-term inflammation of the bronchial tree, increases the risk of developing serious complications such as bronchial asthma and pulmonary infections. Against the backdrop of a deteriorating environmental situation, an increase in the number of allergenic factors, as well as the widespread spread of viral and bacterial infections, the incidence of chronic bronchitis among children is reaching alarming levels.
Keywords: Chronic bronchitis, etiological factors, clinical and laboratory diagnostics, sputum analysis.